Method for manufacturing composite ceramic substrate and composite ceramic substrate

A laminated structure in ceramic substrates using aluminum oxide separation layers prevents phase transformation, enhancing the mechanical properties of alumina-based ceramic substrates for high-power semiconductor packaging by maintaining the reinforcement effects of yttrium-stabilized zirconia and lanthanum oxide.

CN117003565BActive Publication Date: 2024-12-20EDGELESS SEMICON CO LTD OF ZHUHAI +1

Patent Information

Application Number
CN202310943667.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2024-12-20
Estimated Expiration
2043-07-28

AI Technical Summary

Technical Problem

Existing alumina-based ceramic substrates face limitations in mechanical properties due to the transformation of yttrium-stabilized zirconia from a tetragonal phase to a cubic phase when combined with lanthanum oxide at high temperatures, which compromises the overall strength and flexibility of the substrate.

Method used

A manufacturing method involving a laminated structure is introduced, where a first green film of aluminum oxide is interposed between second and third green films of yttrium-stabilized zirconia and lanthanum oxide, respectively, preventing direct contact and phase transformation during high-temperature sintering, thereby maintaining the reinforcement effects of both materials.

Benefits of technology

The method enhances the bending strength of the composite ceramic substrate by ensuring the rod-shaped reinforcement effect of yttrium-stabilized zirconia, resulting in a composite ceramic substrate with improved mechanical properties suitable for high-power and small-sized semiconductor packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117003565B_ABST
    Figure CN117003565B_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a composite ceramic substrate and a composite ceramic substrate. The method for manufacturing the composite ceramic substrate comprises providing a first green film, the first green film being an aluminum oxide green film; providing a second green film, the second green film being made of a first mixture including aluminum oxide and yttrium-stabilized zirconium oxide; providing a third green film, the third green film being made of a second mixture including aluminum oxide and lanthanum oxide; manufacturing a composite body having a multilayer structure by stacking the first green film, the second green film and the third green film, wherein in the composite body, the first green film is arranged between the second green film and the third green film to separate the second green film from the third green film; and sintering the composite body to obtain a composite ceramic substrate having a laminated structure. According to the method for manufacturing a composite ceramic substrate provided by the present invention, the obtained composite ceramic substrate has significantly enhanced flexural strength and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic packaging, and in particular to a manufacturing method of a composite ceramic substrate and the composite ceramic substrate. Background Art

[0002] Ceramic heat dissipation substrates play an irreplaceable role in the field of electronic packaging technology. They mainly provide heat dissipation channels and insulation protection for the carrier chips. Alumina (Al2O3) ceramics, as a type of ceramic heat dissipation substrate, can be widely used in the field of electronic packaging technology because of its advantages such as low cost, abundant sources, high chemical stability, low thermal expansion coefficient and high corrosion resistance. As semiconductor packaging devices gradually develop in the direction of high power, integration, and small size, the field will also put forward higher requirements on the mechanical properties of alumina-based ceramic substrates. Therefore, it is urgent to improve the mechanical properties of alumina-based ceramic substrates. Summary of the invention

[0003] In response to the problems in the above-mentioned related technologies, the present invention provides a method for manufacturing a composite ceramic substrate and a composite ceramic substrate, wherein a first green film formed of aluminum oxide is arranged between a second green film having yttrium-stabilized zirconia (3Y-ZrO2) and a third green film having lanthanum oxide (La2O3), so that the second green film having yttrium-stabilized zirconia and the third green film having lanthanum oxide are separated from each other and do not contact each other, thereby avoiding the presence of La2O3 causing ZrO2 to be transformed from a tetragonal phase to a cubic phase at high temperature, thereby obtaining a composite ceramic substrate with a laminated structure by stacking the first green film, the second green film and the third green film, which can achieve the simultaneous introduction of lanthanum oxide and yttrium-stabilized zirconia into the composite ceramic substrate, and avoid the lanthanum oxide and yttrium-stabilized zirconia contacting each other during high-temperature sintering to affect the overall mechanical properties.

[0004] According to one aspect of the present invention, a method for manufacturing a composite ceramic substrate is provided, the method comprising providing a first green film, the first green film being an aluminum oxide green film; providing a second green film, the second green film being made of a first mixture comprising aluminum oxide and yttrium-stabilized zirconia; providing a third green film, the third green film being made of a second mixture comprising aluminum oxide and lanthanum oxide; manufacturing a composite body having a multilayer structure by stacking the first green film, the second green film and the third green film, wherein, in the composite body having a multilayer structure, the first green film is arranged between the second green film and the third green film to separate the second green film from the third green film; and sintering the composite body to obtain the composite ceramic substrate having a laminated structure.

[0005] In some embodiments, the composite body with a multi-layer structure includes: two outer layer bodies and an inner layer body arranged between the two outer layer bodies, the outer layer body includes a first green layer and a second green layer arranged between the first green layers, and the inner layer body includes a third green layer, wherein the first green layer is formed by at least one first green film, the second green layer is formed by at least one second green film, and the third green layer is formed by at least one third green film.

[0006] In other embodiments, the composite body with a multi-layer structure includes: an outer layer body and an inner layer body arranged between the outer layer bodies, the outer layer body includes a first green layer and a third green layer arranged between the first green layers, and the inner layer body includes a second green layer, wherein the first green layer is formed by at least one first green film, the second green layer is formed by at least one second green film, and the third green layer is formed by at least one third green film.

[0007] In some embodiments, the first green film has a thickness in the range of 100 μm-500 μm; and / or the second green film has a thickness in the range of 100 μm-500 μm; and / or the third green film has a thickness in the range of 100 μm-500 μm.

[0008] In some embodiments, the surface layer of the composite body is a first green layer.

[0009] In some embodiments, the step of providing a second green film includes: providing the first mixture; providing a second additive including a second binder; making the first mixture and the second additive into a second slurry; and making the second slurry into a corresponding second green film.

[0010] In some embodiments, the weight ratio of alumina to yttria-stabilized zirconia is (48-58):(4-14).

[0011] In some embodiments, the particle size of the aluminum oxide is 0.1 μm-1 μm; and / or the particle size of the yttrium-stabilized zirconium oxide is 0.1 μm-0.5 μm.

[0012] In some embodiments, the step of providing a third green film includes: providing the second mixture; providing a third additive including a third binder; making a third slurry with the first mixture and the third additive; and making the third slurry into a corresponding third green film.

[0013] In some embodiments, the weight ratio of aluminum oxide to lanthanum oxide is (48-58):(4-14).

[0014] In some embodiments, the particle size of the aluminum oxide is 0.1 μm-1 μm; and / or the particle size of the lanthanum oxide is 0.05 μm-0.5 μm.

[0015] In some embodiments, the sintering treatment step includes: heating the composite body to 800°C-1200°C at a heating rate of 5°C / min-10°C / min, then heating it to 1550°C-1650°C at a heating rate of 2°C / min-5°C / min, keeping it warm for 1h-2h, then cooling it to 800°C-1200°C at a cooling rate of 2°C / min-5°C / min, and finally cooling it to room temperature with the furnace.

[0016] According to a second aspect of the present invention, a composite ceramic substrate is provided, which has a laminated structure, and the composite ceramic substrate with the laminated structure includes: a first material layer, a second material layer and a third material layer, the first material layer is an aluminum oxide layer, the second material layer is a mixed layer of aluminum oxide and yttrium-stabilized zirconia, and the third material layer is a mixed layer of aluminum oxide and lanthanum oxide, wherein the first material layer is arranged between the second material layer and the third material layer, thereby separating the second material layer and the third material layer.

[0017] In some embodiments, the surface layer of the composite ceramic substrate is a first material layer.

[0018] In some embodiments, the composite ceramic substrate includes: outer covering layers and a core disposed between the outer covering layers, the outer covering layers include a first material layer and a second material layer disposed between the first material layers, and the core includes a third material layer.

[0019] In some other embodiments, the composite ceramic substrate includes: outer covering layers and a core portion disposed between the outer covering layers, the outer covering layers include a first material layer and a third material layer disposed between the first material layers, and the core portion includes a second material layer.

[0020] According to the manufacturing method of the composite ceramic substrate and the composite ceramic substrate of the present application, the LaAl 11 O 18 The rod-shaped reinforcement effect of yttrium stabilized zirconia is guaranteed, thereby significantly enhancing the bending strength of the alumina-based composite ceramic substrate (excellent mechanical properties). BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Hereinafter, the present invention will be described in more detail based on embodiments and with reference to the accompanying drawings.

[0022] Figure 1 A schematic structural diagram of a composite blank provided by an embodiment of the present invention;

[0023] Figure 2 A schematic structural diagram of a composite ceramic substrate provided in an embodiment of the present invention.

[0024] In the drawings, the same reference numerals are used for the same components, and the drawings are not drawn to scale.

[0025] Explanation of symbols

[0026] 10, composite body; 11, outer body; 111, first green body layer; 112, second green body layer; 12, inner body; 121, third green body layer;

[0027] 20. Composite ceramic substrate; 21. Cover layer; 211. First material layer; 212. Second material layer; 22. Core; 221. Third material layer. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings. The described embodiments should not be regarded as limiting the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application.

[0029] In the following description, reference is made to “some embodiments”, which describe a subset of all possible embodiments, but it will be understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.

[0030] If similar descriptions of "first\second\third" appear in the application documents, the following instructions will be added. In the following description, the terms "first\second\third" involved are merely used to distinguish similar objects and do not represent a specific ordering of the objects. It can be understood that "first\second\third" can be interchanged in a specific order or sequence where permitted, so that the embodiments of the present application described herein can be implemented in an order other than that illustrated or described herein.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein are only for the purpose of describing the embodiments of this application and are not intended to limit this application.

[0032] It should be noted that the definitions of the directional terms such as "upper", "lower", "top" and "bottom" in the present invention are based on the orientation of the product when it is placed upright in normal use. It should not be understood as a specific limitation of the embodiments of the present invention. In addition, in the context, it is also necessary to explain that when it is mentioned that one element is connected to another element, it can be either directly connected or indirectly connected, unless it is clearly stated that one element is directly connected to another element.

[0033] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0034] The specific implementation methods of the present invention have been described in detail. Although some embodiments have been shown and described, it should be understood by those skilled in the art that these embodiments can be modified and improved without departing from the principles and spirit of the present invention, the scope of which is defined by the claims and their equivalents.

[0035] In the field of ceramic substrate manufacturing, the introduction of other phases (for example, lanthanum oxide) into the alumina ceramic matrix is ​​a common means of strengthening alumina ceramics. Its strengthening mechanism mainly includes fine grain strengthening, phase transformation strengthening, whisker strengthening, etc. Lanthanum oxide is a common rare earth oxide. The introduction of lanthanum oxide into the alumina ceramic matrix can effectively reduce the grain size of alumina ceramics and achieve fine grain strengthening; and Al2O3 and La2O3 will generate rod-shaped LaAl at high temperature. 11 O 18 , which can effectively enhance the flexural strength of alumina-based ceramics.

[0036] The crystal form of ZrO2 is mainly divided into monoclinic, tetragonal and cubic. Pure ZrO2 is mainly monoclinic. By introducing rare earth elements into ZrO2, the crystal form of ZrO2 will change at a certain temperature. Usually, the mechanical properties of tetragonal ZrO2 are the best, so yttrium is doped into zirconium oxide to obtain yttrium-stabilized zirconia (3Y-ZrO2) with tetragonal crystal form as the main crystal. Yttrium-stabilized zirconia has the characteristics of phase change enhancement and toughening. During the fracture process of ceramics, the crystal form of yttrium-stabilized zirconia will undergo a phase change from tetragonal to monoclinic, thereby consuming a large amount of fracture energy, so it has a phase change enhancement effect. In addition, doping yttrium-stabilized zirconia in the alumina ceramic matrix can also effectively inhibit the growth of alumina grains, and has the effect of fine grain strengthening.

[0037] The above two reinforcement methods of adding other phases to the alumina ceramic matrix can both obtain alumina composite ceramics with certain mechanical properties. However, as semiconductor packaging devices gradually develop towards high power, integration, and small size, the field will also put forward higher requirements on the mechanical properties of alumina-based ceramic substrates. Therefore, it is urgent to improve the mechanical properties of alumina-based ceramic substrates.

[0038] When lanthanum oxide and yttrium-stabilized zirconia are doped simultaneously in alumina ceramics, it is found that the reinforcement effect of the obtained alumina-based ceramic substrate is limited. The reason is that La2O3 will promote the transformation of 3Y-ZrO2 from tetragonal phase to cubic phase at high temperature. The mechanical properties of cubic phase ZrO2 are poor and phase transformation enhancement cannot be achieved during the fracture process, resulting in poor mechanical properties of the alumina-based ceramic substrate.

[0039] According to a first aspect of an embodiment of the present application, a method for manufacturing a composite ceramic substrate is provided, wherein the method for manufacturing a composite ceramic substrate comprises: providing a first green film, wherein the first green film is an aluminum oxide green film; providing a second green film, wherein the second green film is made of a first mixture including aluminum oxide and yttrium-stabilized zirconia; providing a third green film, wherein the third green film is made of a second mixture including aluminum oxide and lanthanum oxide; manufacturing a composite body having a multi-layer structure by stacking the first green film, the second green film and the third green film, wherein, in the composite body having a multi-layer structure, the first green film is arranged between the second green film and the third green film to separate the second green film from the third green film; and sintering the composite body to obtain the corresponding composite ceramic substrate having a laminated structure.

[0040] In the embodiments of the present application, the green film refers to an unsintered film-shaped blank obtained by pressing a powder.

[0041] According to the manufacturing method of the composite ceramic substrate provided in an embodiment of the present application, when the first green film, the second green film and the third green film are stacked in the thickness direction, the first green film formed by aluminum oxide is arranged between the second green film having yttrium-stabilized zirconia and the third green film having lanthanum oxide, so that the second green film having yttrium-stabilized zirconia and the third green film having lanthanum oxide are separated from each other in the thickness direction without contacting each other, thereby avoiding the presence of La2O3 causing ZrO2 to be transformed from a tetragonal phase to a cubic phase at high temperature, so that a composite ceramic substrate with a laminated structure is obtained by compounding the first green film, the second green film and the third green film, which can achieve the simultaneous introduction of lanthanum oxide and yttrium-stabilized zirconia in the composite ceramic substrate, and avoid the mutual contact between lanthanum oxide and yttrium-stabilized zirconia during high-temperature sintering to affect the overall mechanical properties.

[0042] The composite ceramic substrate according to the present application retains LaAl 11 O 18 The rod-shaped reinforcement effect of yttrium stabilized zirconia is guaranteed, thereby significantly enhancing the flexural strength of the alumina-based composite ceramic substrate (excellent mechanical properties).

[0043] Hereinafter, the method for manufacturing the composite ceramic substrate according to the present application will be described in detail in conjunction with specific embodiments.

[0044] Providing a first green film

[0045] In an embodiment, the step of providing a first green film includes preparing a first green film, wherein the step of preparing the first green film includes providing aluminum oxide powder, providing a first additive including a first binder, preparing a first slurry with the aluminum oxide powder and the first additive, and preparing the first green film with the first slurry.

[0046] According to the present application, the alumina powder has a preset particle size, and the particle size of the powder affects the overall strength of the formed composite body. If the particle size is too large, the pores of the formed composite body are too large, and the overall structure of the body is loose, which affects the strength of the composite body; if the particle size is too small, the cost will increase due to the difficulty of the powder making process. In some embodiments, the particle size of the alumina powder is in the range of 0.1 μm-1 μm. Here, the particle size difference of the alumina powder can be made smaller (more uniform), so that the structure at different regions of the first green film is more uniform, thereby ensuring the strength of the formed composite body. The particle size of the above-mentioned material can be the maximum length of the material particles, rather than specifically limiting the material to have a spherical or spherical shape. For example, but not limited to, when the material has an elliptical shape, the particle size of the material can refer to the length of its major axis.

[0047] In some embodiments, a first additive including a first binder is provided. In an exemplary embodiment, the first binder in the first additive may be polyvinyl butyral, which has high bonding strength and good wear resistance, oil resistance and heat resistance. The weight ratio of the alumina powder to the first binder may be (60-70):(3-4).

[0048] According to the present application, the first additive may include an auxiliary agent in addition to the first binder. The auxiliary agent includes a plasticizer and / or a dispersant. In an exemplary embodiment, the plasticizer may be butyl benzyl phthalate, and the dispersant may be triolein. The weight ratio of the alumina powder to the plasticizer may be (60-70):(3-4), and the weight ratio of the alumina powder to the dispersant may be (60-70):(1-2).

[0049] In some embodiments, the step of making the first slurry of the alumina powder and the first additive comprises: mixing the alumina powder and the first additive in a solvent, and then mixing them by a ball mill to make a slurry. In an exemplary embodiment, the solvent is a mixed solvent of polyols, and the mixed solvent of polyols can increase the solubility of the material and can improve the control of drying speed, slurry rheology, cost and safety. Specifically, the mixed solvent of polyols can include n-butanol: isopropanol: anhydrous ethanol, wherein the volume ratio of n-butanol: isopropanol: anhydrous ethanol is (0.5-1): (1-2): (1-2). The weight ratio of the alumina powder and the mixed solvent can be (60-70): (25-35).

[0050] In an exemplary embodiment, 62 parts by mass of alumina powder, 1.2 parts by mass of triolein, 3.1 parts by mass of polyvinyl butyral, and 3.7 parts by mass of butyl benzyl phthalate are first weighed, and then 30 parts by mass of a mixed solvent of polyols (the volume ratio of n-butanol: isopropanol: anhydrous ethanol is 1:2:2) are weighed, the above materials are mixed in the above solvent, and then the ball milling medium is added and mixed evenly by a planetary ball mill (the ball milling speed is set to 250r / min-350r / min, and the time is 6h-10h), thereby preparing an alumina ceramic casting slurry, that is, a first slurry. The first slurry is poured into the material trough of the casting machine, and the scraper height is set to 100μm-500μm, the base belt speed is set to 0.1m / min-0.3m / min, and the drying temperature is 40-55°C, so that the solvent is volatilized and an alumina ceramic green sheet, that is, a first green film, is prepared.

[0051] According to the present application, the thickness of the first green film is in the range of 100 μm-500 μm. The thickness of the green film is determined according to the height of the scraper. When the thickness of the green film is less than 100 μm, the thickness is too thin, resulting in low strength of the green film, and it is easy to crack when peeling the base tape; when the thickness of the green film is greater than 500 μm, the thickness is too thick, resulting in inconsistent drying speeds inside and outside the green film, and the green film is prone to cracking and defects.

[0052] Providing a second green film

[0053] In an embodiment, the step of providing a second green film includes preparing a second green film. The step of preparing the second green film includes: providing a first mixture including alumina powder and yttrium-stabilized zirconia powder, providing a second additive including a second binder; preparing a second slurry with the first mixture and the second additive, and preparing the second green film with the second slurry.

[0054] In the first mixture, the weight ratio of alumina powder to yttrium-stabilized zirconia powder is (48-58):(4-14).

[0055] According to the present application, the powder forming the first mixture has a preset particle size, and the particle size of the powder affects the overall strength of the formed composite body. If the particle size is too large, the pores of the formed composite body are too large, and the overall structure of the body is loose, which affects the strength of the composite body; if the particle size is too small, the cost will increase due to the difficulty of the powder making process. In some embodiments, the particle size of the alumina powder is in the range of 0.1μm-1μm, and the particle size of the yttrium-stabilized zirconia is in the range of 0.1μm-0.5μm. Here, the particle size of the alumina powder and the particle size of the yttrium-stabilized zirconia powder can be made not much different (more uniform), so that the structure at different regions of the second green film is more uniform, thereby ensuring the strength of the formed composite body. The particle size of the above-mentioned material can be the maximum length of the material particles, rather than specifically limiting the material to have a spherical or spherical shape. For example, but not limited to, when the material has an elliptical shape, the particle size of the material can refer to the length of its major axis.

[0056] In some embodiments, a second additive including a second binder is provided, wherein the second binder may be the same as or different from the first binder. In some exemplary embodiments, the second binder may also be polyvinyl butyral, which has high bonding strength and good wear resistance, oil resistance, and heat resistance. The weight ratio of the first mixture to the second binder may be (60-70):(3-4).

[0057] According to the present application, the second additive may include an auxiliary agent in addition to the second binder. The auxiliary agent includes an enhancer and / or a dispersant. The auxiliary agent may be the same as or different from the auxiliary agent used to form the first green film. In an exemplary embodiment, the plasticizer may be butyl benzyl phthalate, and the dispersant may be triolein. The weight ratio of the first mixed material to the plasticizer may be (60-70):(3-4), and the weight ratio of the first mixed material to the dispersant may be (60-70):(1-2).

[0058] In some embodiments, the step of preparing the second slurry with the first mixed material and the second additive comprises: mixing the first mixed material and the second additive in a solvent, and then mixing by a ball mill to prepare the second slurry. In an exemplary embodiment, the solvent is a mixed solvent of polyols, and the mixed solvent of polyols can increase the solubility of the material and can improve the control of drying speed, slurry rheology, cost and safety. In an exemplary embodiment, the mixed solvent comprises n-butanol: isopropanol: anhydrous ethanol, wherein the volume ratio of n-butanol: isopropanol: anhydrous ethanol is (0.5-1): (1-2): (1-2).

[0059] In an exemplary embodiment, 48-58 parts by mass of alumina powder with a particle size of 0.1 μm-1 μm, 4-14 parts by mass of yttrium-stabilized zirconia powder with a particle size of 0.1 μm-0.5 μm, 1.2 parts by mass of triolein, 3.1 parts by mass of polyvinyl butyral and 3.7 parts by mass of butyl benzyl phthalate are weighed, and 30 parts by mass of a mixed solvent of polyols (the volume ratio of n-butanol: isopropanol: anhydrous ethanol is 1:2:2) are weighed, the above materials are mixed in the above solvent, and then ball milling media is added and mixed evenly by a planetary ball mill (the ball milling speed is set at 250r / min-350r / min, and the time is 6h-10h), thereby preparing an alumina / yttrium-stabilized zirconia ceramic casting slurry, i.e., the second slurry. Pour the second slurry into the material trough of the casting machine, set the scraper height to 100μm-500μm, the base belt speed to 0.1m / min-0.3m / min, and the drying temperature to 40-55°C, the solvent evaporates and obtains an alumina / yttrium-stabilized zirconia ceramic green sheet, i.e., the second green film.

[0060] According to the present application, the thickness of the second green film is in the range of 100 μm-500 μm. The thickness of the green film is determined according to the height of the scraper. When the thickness of the green film is less than 100 μm, the thickness is too thin, resulting in low strength of the green film, and it is easy to crack when peeling the base tape; when the thickness of the green film is greater than 500 μm, the thickness is too thick, resulting in inconsistent drying speeds inside and outside the green film, and the green film is prone to cracking and defects.

[0061] Providing a third green film

[0062] In an embodiment, the step of providing a third green film includes preparing a third green film. The step of preparing the third green film includes: providing a second mixture including aluminum oxide powder and lanthanum oxide powder, providing a third additive including a third binder; preparing a third slurry with the second mixture and the third additive, and preparing the third slurry into the third green film.

[0063] In the first mixture, the weight ratio of aluminum oxide powder to lanthanum oxide powder is (48-58):(4-14).

[0064] According to the present application, the powder forming the second mixture has a preset particle size, and the particle size of the powder affects the overall strength of the formed composite body. If the particle size is too large, the pores of the formed composite body are too large, and the overall structure of the body is loose, which affects the strength of the composite body; if the particle size is too small, the cost will increase due to the difficulty of the powder making process. In an embodiment, the particle size of the alumina powder is in the range of 0.1μm-1μm, and the particle size of the lanthanum oxide is in the range of 0.05μm-0.5μm. Here, the particle size of the alumina powder and the particle size of the lanthanum oxide powder can be made not much different (more uniform), so that the structure at different regions of the third green film is more uniform, thereby ensuring the strength of the formed composite body. The particle size of the above-mentioned material can be the maximum length of the material particles, rather than specifically limiting the material to have a spherical or spherical shape. For example, but not limited to, when the material has an elliptical shape, the particle size of the material can refer to the length of its major axis.

[0065] In some embodiments, a third additive including a third binder is provided, wherein the third binder may be the same as or different from the first binder, and the third binder may be polyvinyl butyral, which has high bonding strength and good wear resistance, oil resistance, and heat resistance. The weight ratio of the second mixture to the second binder may be (60-70):(3-4).

[0066] According to the present application, the third additive may include an auxiliary agent in addition to the third binder. The auxiliary agent includes an enhancer and / or a dispersant. The auxiliary agent may be the same as or different from the auxiliary agent used to form the first green film. In an exemplary embodiment, the plasticizer may be butyl benzyl phthalate, and the dispersant may be triolein. The weight ratio of the second mixed material to the plasticizer may be (60-70):(3-4), and the weight ratio of the second mixed material to the dispersant may be (60-70):(1-2).

[0067] In some embodiments, the step of making the second mixed material and the third additive into the third slurry comprises: mixing the second mixed material and the third additive in a solvent, and then mixing by a ball mill to make the third slurry. In an exemplary embodiment, the solvent is a mixed solvent of polyols, and the mixed solvent of polyols can increase the dissolving power of the material and can improve the control of drying speed, slurry rheology, cost and safety. In an exemplary embodiment, the mixed solvent comprises n-butanol: isopropanol: anhydrous ethanol, wherein the volume ratio of n-butanol: isopropanol: anhydrous ethanol is (0.5-1): (1-2): (1-2).

[0068] In an exemplary embodiment, 48-58 parts by mass of alumina powder with a particle size of 0.1 μm-1 μm, 4-14 parts by mass of lanthanum oxide powder with a particle size of 0.05 μm-0.5 μm, 1.2 parts by mass of triolein, 3.1 parts by mass of polyvinyl butyral and 3.7 parts by mass of butyl benzyl phthalate are weighed, and then 30 parts by mass of a mixed solvent of polyols (the volume ratio of n-butanol: isopropanol: anhydrous ethanol is 1:2:2) are weighed, the above materials are mixed in the above solvent, and then ball milling media is added and mixed evenly by a planetary ball mill (the ball milling speed is set to 250r / min-350r / min, and the time is 6h-10h), thereby preparing an alumina / lanthanum oxide ceramic casting slurry, i.e., the third slurry. Pour the third slurry into the trough of the casting machine, set the scraper height to 100μm-500μm, the base belt speed to 0.1m / min-0.3m / min, and the drying temperature to 40-55°C, the solvent evaporates and obtains an aluminum oxide / lanthanum oxide ceramic green sheet, i.e., the third green film.

[0069] According to the present application, the thickness of the third green film is in the range of 100 μm-500 μm. The thickness of the green film is determined according to the height of the scraper. When the thickness of the green film is less than 100 μm, the thickness is too thin, resulting in low strength of the green film, and it is easy to crack when peeling the base tape; when the thickness of the green film is greater than 500 μm, the thickness is too thick, resulting in inconsistent drying speeds inside and outside the green film, and the green film is prone to cracking and defects.

[0070] Forming a composite body

[0071] According to the present application, a composite body having a multilayer structure is obtained by stacking a first green film, a second green film, and a third green film in a thickness direction, and arranging the first green film between the second green film and the third green film so that the second green film and the third green film are separated from each other in the thickness direction;

[0072] According to the present application, the first green film, the second green film and the third green film can be stacked in the thickness direction in a variety of ways to form an initial green body. In an exemplary embodiment, the thickness of each layer in the initial green body can be set based on the thickness of the desired composite ceramic substrate. In some exemplary embodiments, each layer can be formed with a corresponding green film or with multiple corresponding green films. In an exemplary embodiment, when the thickness of the composite ceramic substrate is 0.5mm-1mm, in the initial green body, 1-4 first green films can be used to form a layer of aluminum oxide green layer, preferably, 2-3 first green films can be used to form a layer of aluminum oxide green layer, and 2-6 second green films or third green films can be used to form respective composite green layers, preferably, 3-4 second green films or third green films can be used to form respective composite green layers.

[0073] In order to make the composite substrate stronger, the thickness of the composite green sheet can be made thicker than the thickness of the single alumina green sheet. After the initial green sheet is formed, the initial green sheet is pressed. Specifically, the initial green sheet is placed in a warm isostatic press, and the temperature is set to 100° C., the holding pressure is 30 MPa, and the holding time is 10 minutes, so as to obtain a composite green sheet with good bonding between the layers.

[0074] In some embodiments, the composite body 10 having a multilayer structure includes an outer layer body 11 and an inner layer body 12 disposed between the outer layer bodies 11, wherein the outer layer body 11 includes a first green layer 111 and a second green layer 112 disposed between the first green layer 111, and the inner layer body 12 includes a third green layer 121. The first green layer is formed by at least one first green film, the second green layer is formed by at least one second green film, and the third green layer is formed by at least one third green film.

[0075] In other embodiments, the composite body with a multilayer structure includes an outer layer body and an inner layer body disposed between the outer layer bodies, wherein the outer layer body includes a first green film and a third green film disposed between the first green films, and the inner layer body includes a second green film. The first green layer is formed by at least one first green film, the second green layer is formed by at least one second green film, and the third green layer is formed by at least one third green film.

[0076] like Figure 1 As shown, the composite body 10 with a multilayer structure includes two outer layer bodies 11 and an inner layer body 12 disposed between the two outer layer bodies 11, wherein the outer layer body 11 includes two first green layers 111 and a second green layer 112 disposed between the two first green layers 111, and the inner layer body 12 includes a third green layer 121. The first green layer 111 is formed by two first green films, the second green layer 112 is formed by three second green films, and the third green layer 113 is formed by three third green films.

[0077] The layered structure involves an internal stress problem. Since the thermal expansion coefficients of different material layers are different, the joints between different material layers will be subjected to tensile stress or compressive stress accordingly. The thermal expansion coefficient of 3Y-ZrO2 is greater than that of Al2O3. The surface layer of the composite body is set as the first green layer, that is, the aluminum oxide layer. On the one hand, the aluminum oxide layer on the surface will be subjected to compressive stress. Compared with the case where the surface layer is subjected to tensile stress, the surface layer subjected to compressive stress can greatly increase the bending strength of the substrate, thereby enhancing the internal stress of the formed composite ceramic substrate. On the other hand, for the composite ceramic substrate used for packaging components, the surface needs to be covered with copper, and the thermal expansion coefficients of the aluminum oxide layer and the copper layer on the surface of the composite ceramic substrate are closer, and the interlayer bonding force will be better, which is conducive to the installation of packaging components.

[0078] Degreasing process

[0079] After the composite body is formed, it is necessary to perform a degreasing treatment on the composite body in advance, and the composite body is degreased at a relatively low heating rate and a relatively low temperature so that the additives inside the composite body are removed as much as possible to reduce the influence of the residues of these materials on the overall performance of the composite ceramic substrate. The degreasing treatment steps include: in an air atmosphere, heating to 300℃-400℃ at a rate of 0.5℃ / min-2℃ / min, keeping warm for 1h, and then heating to 550℃-700℃ at a heating rate of 0.5℃ / min-2℃ / min, keeping warm for 30min-2h, and finally cooling to room temperature with the furnace.

[0080] Sintering process

[0081] According to the present application, the initial green body is sintered in a step-by-step heating manner. Specifically, the step of sintering the composite green body in a step-by-step heating manner includes: heating the composite green body to 800°C-1200°C at a heating rate of 5°C / min-10°C / min, then heating it to 1550°C-1650°C at a heating rate of 2°C / min-5°C / min, keeping it warm for 1h-2h, then cooling it to 800°C-1200°C at a cooling rate of 2°C / min-5°C / min, and finally cooling it to room temperature with the furnace.

[0082] In these embodiments, the temperature is raised to between 1550°C and 1650°C and kept warm, which can ensure that Al2O3 and La2O3 generate rod-shaped LaAl 11 O 18 , and adjacent layers are bonded to each other, while ensuring the densification of the structure of the composite substrate.

[0083] According to the second aspect of the present application, a composite ceramic substrate is provided. The composite ceramic substrate is manufactured by the manufacturing method of the composite ceramic substrate provided in each of the above embodiments, and thus has all the beneficial effects of each of the above embodiments, and therefore, will not be described in detail here.

[0084] In some embodiments, the composite ceramic substrate has a laminated structure, and the composite ceramic substrate with the laminated structure includes: a first material layer, a second material layer and a third material layer, wherein the first material layer is an aluminum oxide layer, the second material layer is a mixed layer of aluminum oxide and yttrium-stabilized zirconia, and the third material layer is a mixed layer of aluminum oxide and lanthanum oxide, wherein the first material layer is arranged between the second material layer and the third material layer to separate the second material layer and the third material layer.

[0085] In some embodiments, the surface layer of the composite ceramic substrate is a first material layer.

[0086] In these embodiments, the surface layer of the composite ceramic substrate is the first material layer. On the one hand, the aluminum oxide layer on the surface will be subjected to compressive stress. Compared with the case where the surface is subjected to tensile stress, the compressive stress on the surface can greatly increase the bending strength of the substrate, thereby enhancing the internal stress of the formed composite ceramic substrate. On the other hand, for the composite ceramic substrate used for packaging components, the surface needs to be copper-clad, and the thermal expansion coefficients of the aluminum oxide layer and the copper layer on the surface of the composite ceramic substrate are closer, and the interlayer bonding force will be better, which is beneficial to the installation of packaging components.

[0087] In some embodiments, a composite ceramic substrate includes: an outer covering layer and a core portion arranged between the outer covering layers, wherein the outer covering layer includes a first material layer and a second material layer arranged between the first material layers, and the core portion includes a third material layer, wherein the first material layer is formed by a first green layer formed by at least one first green film through a sintering process, the second green layer is formed by a second green layer formed by at least one second green film through a sintering process, and the third green layer is formed by a third green layer formed by at least one third green film through a sintering process.

[0088] In other embodiments, the composite ceramic substrate includes: an outer covering layer and a core portion arranged between the multiple outer covering layers, wherein the outer covering layer includes a first material layer and a third material layer arranged between the first material layers, and the core portion includes a second material layer, wherein the first material layer is formed by a first green layer formed by at least one first green film through a sintering process, the second green layer is formed by a second green layer formed by at least one second green film through a sintering process, and the third green layer is formed by a third green layer formed by at least one third green film through a sintering process.

[0089] like Figure 2As shown, the composite ceramic substrate 20 includes: two outer covering layers 21 and a core 22 disposed between the two outer covering layers 21 , wherein the outer covering layer 21 includes two first material layers 211 and a second material layer 212 disposed between the two first material layers 211 , and the core 22 includes a third material layer 221 .

[0090] In these embodiments, a second material layer 212 comprising yttrium-stabilized zirconia is sandwiched between two first material layers 211 formed of aluminum oxide to form an outer covering layer 21, and a third material layer 221 comprising lanthanum oxide is disposed between the two outer covering layers 21. The layered structure is arranged based on the thermal expansion coefficients of different materials, which can ensure the internal stress at the junction of each layer in the layered structure, thereby ensuring a better effect of internal stress enhancement and a higher strength.

[0091] According to the present application, the flexural strength of the composite ceramic substrate is not less than 711 MPa.

[0092] It should be understood that "one embodiment" or "an embodiment" mentioned throughout the specification means that specific features, structures or characteristics related to the embodiment are included in at least one embodiment of the present application. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. In addition, these specific features, structures or characteristics can be combined in one or more embodiments in any suitable manner. It should be understood that in various embodiments of the present application, the size of the sequence number of the above-mentioned processes does not mean the order of execution, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application. The above-mentioned sequence numbers of the embodiments of the present application are only for description and do not represent the advantages and disadvantages of the embodiments.

[0093] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0094] The device embodiments described above are only illustrative. For example, the division of the units is only a logical function division. There may be other division methods in actual implementation, such as: multiple units or components can be combined, or can be integrated into another system, or some features can be ignored or not executed. In addition, the coupling, direct coupling, or communication connection between the components shown or discussed can be through some interfaces, and the indirect coupling or communication connection of the devices or units can be electrical, mechanical or other forms.

[0095] The units described above as separate components may or may not be physically separated, and the components displayed as units may or may not be physical units; they may be located in one place or distributed on multiple network units; some or all of the units may be selected according to actual needs to achieve the purpose of the present embodiment.

[0096] In addition, all functional units in the embodiments of the present application may be integrated into one processing unit, or each unit may be a separate unit, or two or more units may be integrated into one unit; the above-mentioned integrated units may be implemented in the form of hardware or in the form of hardware plus software functional units.

[0097] A person of ordinary skill in the art can understand that: all or part of the steps of implementing the above-mentioned method embodiment can be completed by hardware related to program instructions, and the aforementioned program can be stored in a computer-readable storage medium. When the program is executed, it executes the steps of the above-mentioned method embodiment; and the aforementioned storage medium includes: mobile storage devices, read-only memories (ROM, Read Only Memory), disks or optical disks, etc. Various media that can store program codes.

[0098] Alternatively, if the above-mentioned integrated unit of the present application is implemented in the form of a software function module and sold or used as an independent product, it can also be stored in a computer-readable storage medium. Based on this understanding, the technical solution of the embodiment of the present application can essentially or in other words, the part that contributes to the prior art can be embodied in the form of a software product, which is stored in a storage medium and includes a number of instructions for a controller to execute all or part of the methods described in each embodiment of the present application. The aforementioned storage medium includes: various media that can store program codes, such as mobile storage devices, ROMs, magnetic disks, or optical disks.

[0099] The above is only an implementation method of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for manufacturing a composite ceramic substrate, characterized in that: include: Providing a first green film, wherein the first green film is an aluminum oxide green film; providing a second green film, the second green film being made of a first mixture including aluminum oxide and yttrium-stabilized zirconium oxide; providing a third green film, the third green film being made of a second mixed material including aluminum oxide and lanthanum oxide; Manufacturing a composite body with a multi-layer structure by stacking a first green film, a second green film, and a third green film, wherein in the composite body with a multi-layer structure, the first green film is arranged between the second green film and the third green film to separate the second green film from the third green film; The composite green body is sintered to obtain a composite ceramic substrate with a laminated structure.

2. The method for manufacturing a composite ceramic substrate according to claim 1, characterized in that: The composite body with a multilayer structure comprises: an outer layer body and an inner layer body arranged between the outer layer bodies, the outer layer body comprises a first green layer and a second green layer arranged between the first green layers, the inner layer body comprises a third green layer, wherein the first green layer is formed by at least one first green film, the second green layer is formed by at least one second green film, and the third green layer is formed by at least one third green film; or The composite body with a multi-layer structure includes: an outer layer body and an inner layer body arranged between the outer layer bodies, the outer layer body includes a first green layer and a third green layer arranged between the first green layers, and the inner layer body includes a second green layer, wherein the first green layer is formed by at least one first green film, the second green layer is formed by at least one second green film, and the third green layer is formed by at least one third green film.

3. The method for manufacturing a composite ceramic substrate according to claim 1, characterized in that: The thickness of the first green film is in the range of 100 μm-500 μm; and / or the thickness of the second green film is in the range of 100 μm-500 μm; and / or the thickness of the third green film is in the range of 100 μm-500 μm.

4. The method for manufacturing a composite ceramic substrate according to claim 2, characterized in that: The surface layer of the composite body is a first green body layer.

5. The method for manufacturing a composite ceramic substrate according to claim 1, characterized in that: The step of providing a second green film comprises: Providing the first mixed material; providing a second additive comprising a second binder; preparing a second slurry by combining the first mixed material and the second additive; The second slurry is made into a corresponding second green film.

6. The method for manufacturing a composite ceramic substrate according to claim 5, characterized in that: The weight ratio of the aluminum oxide to the yttrium-stabilized zirconia is (48-58):(4-14).

7. The method for manufacturing a composite ceramic substrate according to claim 5, characterized in that: The particle size of the aluminum oxide is 0.1 μm-1 μm; and / or the particle size of the yttrium-stabilized zirconium oxide is 0.1 μm-0.5 μm.

8. The method for manufacturing a composite ceramic substrate according to claim 1, characterized in that: The step of providing a third green film comprises: providing the second mixture; providing a third additive comprising a third binder; preparing a third slurry by combining the first mixed material and the third additive; The third slurry is made into a corresponding third green film.

9. The method for manufacturing a composite ceramic substrate according to claim 8, characterized in that: The weight ratio of aluminum oxide to lanthanum oxide is (48-58):(4-14).

10. The method for manufacturing a composite ceramic substrate according to claim 8, characterized in that: The particle size of the aluminum oxide is 0.1 μm-1 μm; and / or the particle size of the lanthanum oxide is 0.05 μm-0.5 μm.

11. The method for manufacturing a composite ceramic substrate according to claim 1, characterized in that: The sintering treatment steps include: heating the composite green body to 800°C-1200°C at a heating rate of 5°C / min-10°C / min, then heating it to 1550°C-1650°C at a heating rate of 2°C / min-5°C / min, keeping it warm for 1h-2h, then cooling it to 800°C-1200°C at a cooling rate of 2°C / min-5°C / min, and finally cooling it to room temperature with the furnace.

12. A composite ceramic substrate, characterized in that: The composite ceramic substrate has a laminated structure, and the composite ceramic substrate with the laminated structure includes: a first material layer, a second material layer and a third material layer, the first material layer is an aluminum oxide layer, the second material layer is a mixed layer of aluminum oxide and yttrium-stabilized zirconia, and the third material layer is a mixed layer of aluminum oxide and lanthanum oxide, wherein the first material layer is arranged between the second material layer and the third material layer, thereby separating the second material layer and the third material layer.

13. The composite ceramic substrate according to claim 12, characterized in that: The surface layer of the composite ceramic substrate is a first material layer.

14. The composite ceramic substrate according to claim 12, characterized in that: The composite ceramic substrate comprises: outer covering layers and a core portion disposed between the outer covering layers, the outer covering layers comprising a first material layer and a second material layer disposed between the first material layers, and the core portion comprising a third material layer; or The composite ceramic substrate includes: outer covering layers and a core portion disposed between the outer covering layers, the outer covering layers include a first material layer and a third material layer disposed between the first material layers, and the core portion includes a second material layer.

Citation Information

Patent Citations

  • Transparent conductive laminate, and transparent touch panel using the same

    CN101544075A

  • Component for plasma processing apparatus, and method for manufacturing component for plasma processing apparatus

    CN104364887A

  • Al2O3 / ZrO2 composite ceramic based on azeotropic distillation method as well as preparation method and application of Al2O3 / ZrO2 composite ceramic

    CN111620691A

  • Alumina ceramic substrate and preparation method thereof

    CN114988854A

  • High strength aluminium oxide / zironium oxide / lanthanum aluminate complex phase ceramic and its preparation method

    CN1513803A

Cited By

  • Ceramic substrate formed by gel casting of choline hydroxide and preparation method of ceramic substrate

    CN122187507A